Exploring community reading park's role in Sorong City - Rifanto, Dayu; Hufad, Achmad; Hasanah, Viena R (Universitas Padjadjaran, 2024)
Mansapur Community Reading Park, TBI Robert Fulton, and EGAD Kairos Reading House are community reading parks in Sorong that aim to increase the community's reading interest. Reading remains a significant issue in Indonesia, especially in Papua. This research aimed to identify community reading parks' efforts, supporting and inhibiting factors, and their contributions to enhancing reading interest. The research method used was a descriptive qualitative case study. Three informants from TBI Robert Fulton, EGAD Kairos Reading House, and Mansapur Community Reading Park were interviewed, and then observations and documentation studies were conducted. The study found that various efforts were made by community reading parks, including collaboration with other communities, foundations, and the government as supporting factors. However, there were also issues, such as a need for more human resources and books and problems with the location of reading parks. The study also found that community reading parks contributed to increasing reading interest. The conclusion this study concludes that despite facing various challenges, these three community reading parks provide efficiently accessible spaces, serve as sources of reading and recreation through various activities, build partnerships with many parties, and promote literacy through social media campaigns. The study also needs to identify gaps in their role as academic or research reference sources.